Persistent left superior vena cava presenting as brain abscess: A case report - Neha Mohan Rao; Guruprasad Hassan Shankar; Bhakti U Sarangi; Sanjay Bafna; Priscilla Joshi; Rahul Jahagirdar (Wolters Kluwer Medknow Publications, 2021)
A persistent left superior vena cava (PLSVC) draining into the left atrial appendage can exist as an unidentified right-to-left shunt often with no demonstrable evidence of hypoxia on history but predisposing to life-threatening clinical implications. We present a 7-year-old boy with a brain abscess who was incidentally noted to have features of hypoxia on examination. His evaluation revealed the presence of a PLSVC on computed tomography pulmonary angiogram, draining into the left atrium, thereby acting as a right-to-left shunt explaining the brain abscess. He underwent a craniotomy with a course of intravenous antibiotics, remained well on follow-up, and was referred for definitive surgery for PLSVC. Children with unidentified right-to-left shunts may present with brain abscesses in the event of which both intracardiac and extracardiac shunts have to be ruled out with the help of history, a focused clinical assessment, and more advanced imaging.